Third Five Year Plan Progress Report 1964-65 Government of Rajasthan - Planning Commission (Planning Commission, 1964)
The Indian economy was under considerable pressure during 1964-65. Three aspects of economic situation which caused anxiety were the rising trend in prices, the difficulties in raising adequate resources for investment and the sharp decline in the foreign exchange resources. The price situation continued to pose a serious problem for the Indian economy. The pressure on prices that had set in the previous years was further aggravated. However as the prospects of Agricultural production in 1964-65 indicated substantial increase over the previous year and the arrivals in markets improved, there was an easing of general price level in the middle of January, 1965, which continued till the end of the year.
Government of Rajasthan Directorate of Economics and Statistics Rajasthan, Jaipur